Reading Level Distribution in School Districts: Implications for Curriculum Enhancements - Bacus, Remedios; Alda, Rivika; Balo, Vincent Theodore; Arandia, Nestor (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Reading is a core component of standardized tests and a cornerstone of academic success, prompting schools in the basic education to invest in reading programs for elementary learners. This study investigates the reading levels of Grades 4 to 6 students, analyzes reading performance trends across grade levels and school districts, and proposes curriculum enhancements in school districts in Cebu City, Philippines. Utilizing a cross-sectional study design, reading proficiency data were analyzed using frequency distribution and chi-square tests. Results indicate an overall improvement in reading levels, with a higher percentage of students moving from Frustration to Instructional reading levels, particularly in the North District. However, ongoing difficulties exist in the South District, where many higher-grade students remain at the Frustration level. Gender analysis reveals that females tend to demonstrate higher reading levels compared to males, with the difference becoming more pronounced from Grade 5 onward. Targeted curriculum enhancements like reading intervention programs in Grade 4 may support struggling readers, while teachers may benefit from professional development on culturally responsive reading strategies to improve reading instruction and promote literacy outcomes across district schools.